Visual Cortex: The Eccentric Area Prostriata in the Human Brain - Tamietto, Marco (Curr Biol, 2018)
Human Area Prostriata is a small, unstudied portion of the visual brain set deep in the calcarine sulcus, next to V1. A recent neuroimaging study in humans indicates that this area is specialized to respond to rapidly moving stimuli in the far periphery, consistent with single-unit responses in other mammals.